PENGGUNAAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN KARTU “SULANG MAYA” DALAM MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR PENDIDIKAN AGAMA HINDU SISWA KELAS VII A SMP NEGERI 1 BANGLI TAHUN PELAJARAN 2018/2019 - I Nengah Asrama Juta Ningrat; Ayu Veronika Somawati (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
This study aims to increase student activity and learning outcomes through the use of the use of the Problem Based Learning Model assisted by Sulang-Maya cards in class VII A students of SMP Negeri 1 Bangli in the 2018/2019 learning year in the subject of Hindu Religious Education. Sulang-Maya card is an acronym for rearranging the card-based yadnya learning material which contains pictures of the implementation of the yadyna ceremony. The steps for using the Sulang-Maya card are as follows: a) the teacher provides an overview of yadnya learning material in the form of attractive illustrations and pictures, b) the teacher presents the yadnya learning material in the form of card pieces and distributes pictures of the various yadnya implementation to students, c) students in groups actively pair the pictures of the yadnya ceremony which are distributed according to the parts of the Panca Yadnya, d) the teacher intensively provides explanations to students so that students are active in doing assignments, e) students and their group members actively explain the results of their group work in front of the class, and f) the teacher reflects on the results of learning activities. Data collection techniques in this study were tests and observations, and the data from the research results were analyzed using qualitative descriptive analysis. The results showed that through the use of the Problem Based Learning Model assisted by Sulang-Maya cards in class VII A students of SMP Negeri 1 Bangli in the 2018/2019 learning year, it could increase activity and learning outcomes in Hindu Religious Education subjects.